(3GdTQYjI GdOhdjI ddOhdI Hjf GdbGfhf GdOhdj hGdabg GdESdGej (B/s - (3GdUZjQ, YHO GdYRjR eMeOs ((3GdbGgQI (B:s (3GdeQcR Gdbhej ddEUOGQGJ GdbGfhfjI,s, 2015)
(3jJMOK gPG GdcJGH Yf GdTQYjI GdOhdjI ddOhdI Hjf GdbGfhf GdOhdj hGdabg GdGSdGej Ef GdTQYjI GdOhdjI ddOhd bO XgQJ efP HQhR GdOhdI GdMOjKI hPdc aj GdJGQjN GdeYGUQ hEPG cGf GdHYV jQLY GdaVd dPdc ddYdGeI LGf HhOGf aj JaUjd hJMOjO eOdhd GSJYeGd gPG Gdeaghe hacQI GdTQYjI GdOhdjI Ch GdGYJQGa HGdOhdI aj GdeLJeY GdOhdj GdYGe gj faSgG acQI GdSjGOI hYdi VhA Pdc jbOe gPG GdcJGH OQGSI HYfhGf GdTQYjI GdOhdjI ddOhdI Hjf GdbGfhf GdOhdj hGdabg GdESdGej hjbY GdcJGH aj KdGKI aUhd GdbGfhf GdOSJhQj hfTCI hJWhQ GdfXGe GdOhdj hSjGOI GdOhd aj Xd JMhdGJ ehGRjf GdbhI aj GdfXGe GdOhdj(B. s
(3GdeMJhjGJ (B: (3GdbGfhf GdOSJhQj(B-(3GdeYjGQ GdTcdj hGdehVhYj ddbGfhf GdOSJhQj(B-(3fTCI eHOC GdSjGOI(B-(3GdSdWI GdSjGSjI hGdSjGOI(B-(3GdSjGOI aj GdOhdI GdESdGejI(B-(3GdSjGOI aj GdacQ GdZQHj(B-(3fTCI hJWhQ GdfXGe GdOhdj(B-(3edGeM GdJZjQ aj GdfXGe GdOhdj(B-(3GdCee GdeJMOI Hjf GdTQYjI hJfGbV GdSjGSI GdOhdjI(B-(3GdSjGSI GdNGQLjI GdCeQjcjI hGdYdGbGJ GdOhdjI(B-(3edGeM hTcd GdfXGe GdOhdj GdLOjO(B-(3SjGOI GdOhd aj Xd ehGRjf(B-(3GdbhI aj GdfXGe GdOhdj(B-(3GdfXGe GdSjGSj GdOhdj(B-(3GdSjGSI GdNGQLjI ddOhdI(B-(3GdJYGhf Hjf GdOhd(B-(3JbSjeGJ GdHfjI GdOGNdjI ddOhdI(B-(3GdeQcRjI hGddGeQcRjI GdEOGQjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B233-245.s
Keywords: (3GdbGfhf GdOhdjs; (3GdESdGe hGdbGfhf GdOhdjs